Vibration analysis of membrane by time average in-line digital holographic interferometry - Singh, Vijay Raj (2011)
In this paper, in-line digital holography is combined with time average method and applied for vibration analysis of an aluminum membrane. The numerically reconstructed wave from time average holograms contains information of mode shape and mean deformation of the vibrating objects. At lower amplitudes of vibration only the deformation fringes are observed and as the amplitude is increases, the Bessel fringes representing the time average vibration amplitude also become visible. Experimental results for a 10mm size membrane are presented.